2022
DOI: 10.3390/cancers15010079
|View full text |Cite
|
Sign up to set email alerts
|

Updated Mortality Analysis of SELTINE, the French Cohort of Nuclear Workers, 1968–2014

Abstract: Cohorts of nuclear workers are particularly relevant to study the health effects of protracted exposures to low doses at low dose-rates of ionizing radiation (IR). In France, a cohort of nuclear workers badge-monitored for external IR exposure has been followed-up for several decades. Its size and follow-up period have recently been extended. The present paper focuses on mortality from both cancer and non-cancer diseases in this cohort. The SELTINE cohort of nuclear workers employed by CEA, Orano, and EDF comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The reasons for differences between the Mayak study and INWORKS are unclear, but in the early years of operation at the Mayak facilities many workers were highly exposed with substantial uncertainty about their internal and external radiation doses 2857. Analyses of mortality among French nuclear workers showed a positive association between estimated colon dose and solid cancer mortality (excess relative rate 0.69 (95% confidence interval −0.28 to 1.77) per Gy)58; we note that INWORKS includes a sizable fraction of this cohort. Analyses of mortality among US nuclear workers showed a positive association between cumulative dose and solid cancer mortality (excess relative rate 0.19 (95% confidence interval −0.10 to 0.52) per Gy), which was of larger magnitude among workers first hired after 196059; again, we note the overlap between this cohort and INWORKS.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for differences between the Mayak study and INWORKS are unclear, but in the early years of operation at the Mayak facilities many workers were highly exposed with substantial uncertainty about their internal and external radiation doses 2857. Analyses of mortality among French nuclear workers showed a positive association between estimated colon dose and solid cancer mortality (excess relative rate 0.69 (95% confidence interval −0.28 to 1.77) per Gy)58; we note that INWORKS includes a sizable fraction of this cohort. Analyses of mortality among US nuclear workers showed a positive association between cumulative dose and solid cancer mortality (excess relative rate 0.19 (95% confidence interval −0.10 to 0.52) per Gy), which was of larger magnitude among workers first hired after 196059; again, we note the overlap between this cohort and INWORKS.…”
Section: Discussionmentioning
confidence: 99%
“…The survey data collected as part of this study does not accommodate previous work experience, which may influence the calculation of the years of experience in some cases. Lastly, these data were collected from an occupational cohort and may be susceptible to the healthy worker effect: individuals more heavily impacted by the exposures faced on their job may have left earlier and be underrepresented in the study (Laurent et al, 2023; Wen & Tsai, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…For dementia, the early nested case-control study found association with radiation exposure in US female nuclear workers with OR of 2.09 (95% CI: 1.02, 4.29) for mortality (214), and then the INWORKS study found ERR/Sv of 1.30 (90% CI: 0.23, 2.72) for mortality due to mental and behavioral disorders in which dementia explained 53% deaths (121). In French male nuclear workers, ERR/Gy was -1.30 (95% CI: not estimated, 7.44) for Parkinson's disease mortality, but was 9.62 (95% CI: 3.05, 18.68) for mortality from dementia and Alzheimer's disease (215). The most recent systematic review of epidemiological literature published by November 2022 and its meta-analysis for incidence and mortality showed mERR/100 mGy of 0.11 (95% CI: 0.04, 0.18) for dementia, Parkinson's disease and Alzheimer's disease in aggregate and 0.12 (95% CI: 0.07, 0.17) for Parkinson's disease (216).…”
Section: Other Late-occurring Noncancer Effects On the Radarmentioning
confidence: 98%